PENGARUH PRICE SENSITIVITY DAN ENVIRONMENTALISM TERHADAP PURCHASE INTENTION PADA PAKAIAN THRIFT - Mentari Septynaputri Widodo; Sadana Devica (Politeknik Ubaya, 2022)
Abstract A person's need for fashion is also always growing, with the need for fashion, now the trend of thrift clothes is also developing, which is known as thrifting. Thrifting is an activity to buy used goods, especially clothing with the aim of helping to reduce environmental pollution produced by fast fashion activities. Indonesian consumers' interest in these thrift goods is increasing over time. Where the data shows that the level of consumption of thrift clothing has increased by 21 percent in the last three years. Based on several previous studies, there are several things that affect a person's purchase intention in buying thrift goods. Among them are environmentalism and price sensitivity.The aim of this study is to investigate the unique characteristics of these consumers and offer a better understanding of the specific drivers of thrift product consumption. In particular, this study explores the reality (or lack thereof) of a number of assumptions regarding the consumption of thrift goods. Thisresearch was conducted on 106 students. Data were processed using confirmatory factor analysis (CFA) and regression analysis. Testing using the structural equation model (SEM) shows that price sensitivity has a significant effect on purchase intention, while a person's level of environmentalism is found to have no effect on purchase intention.